Development of students’ ecological culture during the realisation of heuristic approach to learning - Dyubkova-Zhernosek, Tatyana P. (Journal of the Belarusian State University. Sociology, 2024)
The role of heuristic learning in the development of students’ ecological culture is justified when they master the academic discipline «Human life safety». The results of a heuristic Internet lesson conducted at the Belarusian State University in several stages as part of the guided independent work of 1st and 2nd year students are presented. The main element of heuristic training was an open task. The formulations of educational goals presented in the open assignment assumed various types of student activity, the dominant of which was creative activity. It is noted that the main result of students’ creative self-realisation with a heuristic approach to learning in the field of waste management is personal educational increment, both external (in the form of a materialised product of independent educational activity) and internal (in the form of the evolution of environmental knowledge, skills, mastered ways of activity, worldview, personal cognitive, creative, value-based-semantic and other qualities). It is concluded that heuristic learning is an effective tool for the development of students’ ecological culture. Their personally significant discoveries of the world around them require the involvement of knowledge from different fields and a critical understanding of the information received, which contributes to the formation of a new understanding of the environmental problem and the development of the ability to produce knowledge. Creative self-realisation changes students’ emotional and value attitude to the surrounding reality and influences the formation of their environmental behaviour. It is emphasised that the ability to find a non-standard approach to solving a problem within the framework of active environmental behaviour depends not only on the totality of acquired knowledge, but also on the personal qualities of the student. The interrelation of the external and internal components of educational products is the basis for the transformation of the system of environmental value orientations of an individual and the formation of an ecocentric worldview.
Keywords: ecological culture; heuristic approach to learning; human life safety; open type task; educational product; student’s personal qualities